Effects of manure and chemical fertilizers on maize performance in the steep hillside with and without terraces in North Halmahera, Indonesia - Rofita Rofita; Sri Nuryani Hidayah Utami; Azwar Maas; Makruf Nurudin (Jurnal Ilmu Pertanian, 2022)
Improper soil management inland with steep slopes is one of the causes of decreased agricultural productivity in hilly areas. The use of terraces on steep slopes is considered effective in preventing erosion. However, this does not increase agricultural productivity significantly. Therefore, this study aimed to analyze the performance of maize on land with and without terraces as affected by the addition of goat manure and NPK. A field experiment was arranged in a randomized complete block design, consisting of 12 experimental plots that were made on a hill with a slope of 79 % with three replications. Plant tissue samples were analyzed for assessing N, P, and K content. However, soil samples were measured for N, P, K, SOC, pH H2O, EC, CEC, and soil texture. Data were analyzed using analysis of variance and continued with a Post-Hoc test (DMRT at α= 5%). The application of manure and NPK fertilizers significantly improved EC, SOC, N, and P in soil, also N and P content in plant tissues. Goat manure played a role in improving soil properties, while NPK fertilizers played a role in supplying nutrient availability directly to plants. The best performance of maize was on land without terraces and cover crops (sweet potato). Competition for nutrients between maize and sweet potato occurred on land with terraces so that the performance of maize tended to be lower. Soil management on land with terraces needs to consider nutrient management and selection of cover crops so that both can increase maize productivity.